Determinants of Lecturer Performance through Competencies, Leadership, Academic Culture, and Technology Mastery - Ariyanto Masnun; Havidz Aima; Zefri Yenni (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Lecturer performance is a central factor in improving the quality of higher education, as it reflects the ability of educators to fulfill the Tri Dharma of Higher Education. Previous studies have often measured lecturer performance using reflective indicators, but limited research has examined performance through formative indicators, particularly in the context of private universities. This study aims to determine, analyze, and measure the direct and indirect effects of leadership, academic culture, competence, and technology mastery on lecturer performance. The research employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). A total of 410 lecturers from private universities in Jambi Province were selected as respondents. The analysis results showed that six of the ten proposed hypotheses were supported. Academic culture, technology mastery, and competence had significant direct effects on lecturer performance. Furthermore, academic culture and technology mastery demonstrated significant indirect effects on performance through competence. In contrast, leadership did not show a significant direct or indirect influence. The findings highlight that competence has the strongest impact on lecturer performance, with its effectiveness enhanced by supportive academic culture and technology mastery relevant to contemporary educational demands.